Determining Misbehaviors Encountered by Physical Education Teachers and Their Opinions about the Methods Used Against to Those Behaviors - Anıl Onur Mercanoğlu (Journal of Educational Issues, 2024)
Determining the misbehaviors encountered in physical education classes and the methods used against these behaviors is important both in terms of producing new solutions by revealing the current situation in classroom management and providing a preliminary information for teachers who will just start the profession. The aim of the study is to determine the physical education teachers’ views who work at schools in Yenimahalle district in Ankara about student misbehaviors and their opinions about the methods used against to those behaviors in physical education lessons. The research group consists of 100 physical education teachers in total who were chosen with convenience sampling method and work at public schools in Yenimahalle district. The questionnaire used to collect data consists of two parts. In the first part, there are items related to student misbehaviors. In the second part, there are items related to the methods used against student misbehaviors. The four-point Likert rating system was applied and the items were rated as “never”, “seldom”, “usually”, “always”. According to the findings, it revealed that the misbehavior most frequently encountered by physical education teachers is “complaining about friends to the teacher” and the misbehavior that they usually meet is “talking in class without asking permission”. It was determined that the methods most frequently used by the physical education teachers in the research group were “rewarding positive behaviors” and “attracting students’ attention to the lesson by asking questions about the subject of the lesson”. It can be stated that these results will serve as a guide especially in the preparation process of physical education teacher candidates.